User engagement with social media, implication on the library usage: a case of selected public and academic libraries in Malaysia - Shafawi, Sharyna; Hassan, Basri (University of Idaho Library, 2018)
The mainstream use of social media has impacted the library as it has been identified to be an efficient platform for libraries to foster networking and enhance engagement with their user community. The unique characteristics of social media with ‘high tech’, ‘interactive’ blend with the ‘human touch’ give a valuable means for libraries to provide information resources and services beyond their physical walls. However, despite its widespread usage, an engagement rate on social media is still low among library users and evaluation of social media use is still elusive and scarce in the library literature. Prior studies have yet to reveal to what extent the presence of social media triggers users’ awareness and influence their engagement. Subsequently, how it further impacts the actual library usage among end-users. Therefore, the present study attempts to investigate the factors that drive users’ engagement with social media and further examine the relationship of users’ engagement with social media and actual library use from both users and librarians’ perspectives. A mixed method approach was employed, and the study population consists of selected State Public and Academic Libraries in Malaysia. The integration of DeLone and McLean’s Information Systems Success Model (ISSM), Perceived Interactivity (PI) and Consumer Online Engagement (COE) models were adapted to establish the direction of the research. A total of 334 respondents which consisted of library users; and 11 interview participants comprise of professional librarians. The statistical data was analysed usingSPSSand SmartPLS, while thematic analysis was employed for the qualitative approach. The findings indicated that Information Quality, Perceived Interactivity, and Perceived Net Benefit have empirically proven to be significant predictors of users’ engagement with social media. The study also revealed that two dimensions of online engagement (affective and behavioural) have a positive and statistically significant effect on actual library use; while cognitive engagement proves to be insignificant. The study is significant in providing libraries a holistic overview about determinants of social media engagement and offers guidelines on evaluation of library social media. It also explored the potential and gauges the prospective areas of improvement for harnessing the use of library resources and services in meeting users’ ever-changing needs. Finally, the study proposed a framework for social media engagement evaluation for libraries which act as a benchmark to determine the best social media platforms to be adopted by libraries. Furthermore, the proposed criteria can be applied to increase users’ awareness and greater users’ engagement of library services.